On the “mise-en-scène” of Pinoocchio 1940 and 2022 films' versions - Cha, Mi Song; Ruslianti, Atikah; Kusuma, Dwi Linda (Lililacs Journal, 2024)
This study examines the film Pinocchio (2022) by Robert Zemeckis in comparison to the 1940 version of old animation on the basis of mise-en-scène. The analysis was done using the descriptive analysis method with the film approach and the films are analyzed on both the narrative and cinematographic aspect. The result showed that two films show a lot of similarities since they were both made on the same story. The analysis of the narrative aspect showed that they have different opening and conclusion in plot, have extra more characters in the new film, as well as show different social setting of the film. The cinematic examination proved that the new film put more details on the props of cuckoo clocks made by Geppetto and the lighting analysis showed that the 1940 version used constant high-key lighting while the new version used both low-key and high-key lighting. The 2022 version also used various camera angles and movements, while the 1940 version used constant standard camera angles throughout the film. The overall analysis showed that while the old version is made simply for young audiences, the new film targets audiences of not only young children, but also young adults.